Conservation Rates of Breast and Axilla Indicate the Quality of Surgical Management of the Early-Stage Breast Cancer Patient: Quality in breast surgery - Peterko, Ana; Grebić, Damir; Juranić, Damir; Bila, Aleksandra; Trčak, Danijel; Brajan, Dolores; Žepina, Nevija; Golubovac Iskra, Mladenka; Lovasić, Franjo (Archives of Breast Cancer, 2022)
Background: Multidisciplinary care in quality-assured specialized Brest Centre (BC) is nowadays considered optimal management of breast cancer and is associated with better patient outcomes. Modern breast cancer surgery should provide optimal oncological outcomes and preserve the quality of life. European Society of Breast Cancer Specialists (EUSOMA) set up the minimum requirements for a specialized BC and a set of 15 mandatory quality indicator (Q.I.) benchmarks for BC certification purposes. Six Q.I. are intended for breast cancer surgery quality assessment. Methods: In BC of Clinical Hospital Centre Rijeka, data were collected retrospectively for 2019 and prospectively thereafter in a clinical register, encrypted according to the EUSOMA instructions and uploaded into collective EUSOMA database. Following database validation, all Q.I. were calculated for our BC for 3 consecutive years. In addition, a comprehensive on-site audit was performed in 2021 for all services included in breast cancer management in Rijeka. Results: All mandatory surgical Q.I. were above the EUSOMA benchmarks in all 3 years. Non-compliance with EUSOMA recommendations were reported as major, minor, recommendations and observations. For BC surgical department, no major or minor non-conformities were reported. At the national level, mastectomy rates were above the permitted EUSOMA benchmark in 4 consecutive years. Conclusion: We have voluntarily initiated and performed quality control of our BC. The certificate obtained is a confirmation of the high quality of care. Concerning the mastectomy rate in Croatia, other centres should consider quality evaluation to determine the status of detected suboptimal surgical management.